Heparin-based hydrogel scaffolding alters the transcriptomic profile and increases the chemoresistance of MDA-MB-231 triple-negative breast cancer cells. (24th February 2020) - Menon, Nidhi; Dang, Ha X.; Datla, Udaya Sree; Moarefian, Maryam; Lawrence, Christopher B.; Maher, Christopher A.; Jones, Caroline N.
Abstract : The solid-phase presentation of growth factors in heparin-based hydrogel alters the transcriptomic profile and increases the chemoresistance of MDA-MB-231 cells. Abstract : The tumor microenvironment plays a critical role in the proliferation and chemoresistance of cancer cells. Growth factors (GFs) are known to interact with the extracellular matrix (ECM) via heparin binding sites, and these associations influence cell behavior. In the present study, we demonstrate the ability to define signals presented by the scaffold by pre-mixing growth factors, such as epidermal growth factor, into the heparin-based (HP-B) hydrogel prior to gelation. In the 3D biomimetic microenvironment, breast cancer cells formed spheroids within 24 hours of initial seeding. Despite higher number of proliferating cells in 2D cultures, 3D spheroids exhibited a higher degree of chemoresistance after 72 hours. Further, our RNA sequencing results highlighted the phenotypic changes influenced by solid-phase GF presentation. Wnt/β-catenin and TGF-β signaling were upregulated in the cells grown in the hydrogel, while apoptosis, IL2-STAT5 and PI3K-AKT-mTOR signaling were downregulated. With emerging technologies for precision medicine in cancer, this nature of fine-tuning the microenvironment is paramount for cultivation and downstream characterization of primary cancer cells and rare circulating tumor cells (CTCs), and effective screening of chemotherapeutic agents.